Elucidative analysis and sequencing of two respiratory health monitoring methods to study the impact of varying atmospheric composition on human health. (December 2017) - Awasthi, Amit; Hothi, Navjot; Kaur, Prabhjot; Singh, Nirankar; Chakraborty, Monojit; Bansal, Sangeeta
Abstract: Atmospheric composition of ambient air consists of different gases in definite proportion that affect the earth's climate and its ecological system. Due to varied anthropogenic reasons, this composition is changed, which ultimately have an impact on the health of living beings. For survival, the human respiratory system is one of the sensitive systems, which is easily and closely affected by the change in atmospheric composition of an external environment. Many studies have been conducted to quantify the effects of atmospheric pollution on human health by using different approaches. This article presents different scenario of studies conducted to evaluate the effects on different human groups. Differences between the studies conducted using spirometry and survey methods are presented in this article to extract a better sequence between these two methodologies. Many studies have been conducted to measure the respiratory status by evaluating the respiratory symptoms and hospital admissions. Limited numbers of studies are found with repeated spirometry on the same subjects for long duration to nullify the error arising due to decrease in efforts by the same subjects during manoeuvre of pulmonary function tests. Present study reveals the importance of methodological sequencing in order to obtain more authentic and reliable results. This study suggests that impacts of deteriorating atmospheric composition on human health can be more significantly studied if spirometry is done after survey analysis. The article also proposes that efficiency and authenticity of surveys involving health impacts will increase, if medical data information of patients is saved in hospitals in a proper format. Graphical abstract: Classification of different studies in the field of respiratory. Highlights: Methodological retrospection of varied atmospheric composition on respiratory health is studied. Better sequence among two methodologies i.e., Spirometry and Survey is proposed. To avoid the impact of efforts done during maneuver, repeated spirometry is avoided. Spirometry should be done post survey to quantify the impacts obtained from survey. Predefined common application software should be installed for survey method.